Adherence to Stroke Care Performance Measures in Different Regions in China, 2015–2019: Evidence From the Chinese Stroke Center Alliance. (18th October 2022) - Zheng, Suxi; Zhang, Tong; Gu, Hong-Qiu; Zhang, Zi-Qin; Yang, Xin; Wang, Chunjuan; Li, Hao; Jiang, Yong; Shen, Haipeng; Li, Zixiao; Wang, Yongjun
Abstract : Background and Objectives: To explore the regional discrepancy of the adherence to guideline-recommended stroke interventions for the stroke belt division (north vs south), the economic development division (east vs middle vs west), and potential interaction. Methods: We conducted a retrospective observational study using data from the Chinese Stroke Center Alliance from August 2015 to August 2019. The primary outcome was hospital personnel adherence to 11 individual guideline-recommended treatments. The coprimary outcomes included 2 summary measures: a composite score (range, 0 [nonadherence] to 1 [perfect adherence]) and an all-or-none binary outcome for adherence to evidence-based stroke. Regional disparities were assessed according to the stroke belt division and the economic development division and the interaction between these 2 divisions. Multivariate regression models with generalized estimating equations were used to analyze the outcomes. Results: This study included 838, 229 patients with acute ischemic stroke from 1, 473 hospitals. The overall quality of care in the nonbelt regions (southern China) was higher than in the stroke belt regions (northern China), as reflected by a higher composite score (0.77 vs 0.75; adjusted odds ratio 1.03 [95% CI 1.02–1.04]; p < 0.001) and a higher all-or-none measure (25.5% vs 22.0%; 1.32 [1.17–1.49], p < 0.001). Patients in the East and Central had higher odds of using intravenous tissue-type plasminogen activator (East: 1.81 [95% CI 1.51–2.18], p < 0.001; Central: 1.57 [95% CI 1.26–1.95], p < 0.001), early antithrombotic medications (East: 1.77 [1.49–2.11], p < 0.001; Central: 1.37 [1.12–1.66], p < 0.001), lipid-lowering medications (East: 1.29 [1.08–1.53], p < 0.001), and deep vein thrombosis prophylaxis (East: 1.28 [1.08–1.50], p = 0.003) compared with those in the West. Patients in the nonbelt regions had higher odds of getting dysphagia screening (1.82 [1.55–2.13], p < 0.001) and rehabilitation assessment (which though varied among different economic development levels). Reflected by significant interaction effects, for patients in the East, those in the nonbelt regions had greater odds of receiving anticoagulation (1.62 [1.34–1.96]; p < 0.001) but lower odds of receiving antithrombotic (0.63 [0.52–0.77]; p < 0.001) and antidiabetic medications (0.87 [0.77–0.99]; p = 0.03); for patients in the West, those in the nonbelt regions were less likely to receive antihypertensive (0.64 [0.46–0.88]; p = 0.004) and antidiabetic (0.66 [0.54–0.81]; p < 0.001) medications. Discussion: Stroke care performance measures differed across regions, along the stroke belt division, and the economic development division. The overall quality of care in the non–stroke belt regions was higher than that in the stroke belt regions. The 2 divisions had interaction effects on several individual measures.